School Counselors’ Vital Role in Suicide Intervention: A Response to Gallo and Wachter Morris - Carolyn Stone (Teaching and Supervision in Counseling, 2022)
School counselors have a critically important role in suicide intervention, one that provides the greatest chance to ensure student safety. In this response article, I clarify the intent of the American School Counselor Association magazine column, "Suicide Assessments: The Medical Profession Affirms School Counselors’ Truth," to underscore the critical role that school counselors play in suicide intervention. School districts are requiring school counselors to quantify suicide and make a judgment based on the student’s self-report. The intended message of the column was not to diminish school counselor training in suicide assessment and intervention, instead it was to provide school counselors a tool in their advocacy efforts to move from district requirements to quantify suicide to the more powerful role of information gatherer. Working within this role, school counselors assist parents/guardians in seeking external counseling professionals who can provide tools not available in schools, such as family therapy, residential treatment, medication, hospitalization, treatment plans, and intensive therapy.
Keywords: suicide; assessments; school counselors; mental health providers